HUBUNGAN BEBAN KERJA DAN STRES KERJA PERAWAT TERHADAP KEPATUHAN HAND HYGIENE MASA PANDEMI COVID-19 DI RSUD CILINCING - Nur Fitriah Efendy (2021)
Nurses play major role in infection prevention and control. Hand hygiene is known as the most effective measure in preventing and controlling the spread of infection in health facilities. The outbreak of COVID-19 has caused high number of virus spreads, in this situation hand hygiene has a very important role. The workload and job stress can affect nurses hand hygiene compliance. The purpose of this study was to analyze the relationship between workload and job stress of nurses with hand hygiene compliance during the Pandemic COVID-19 at Cilincing Hospital. This research is quantitative research with analytical descriptive using a cross-sectional. Sampling technique used is total sampling with total of 22 respondents join this research. Chi-square test used to analyze the data. The results of this study indicate that there is a significant relationship between workload (P value = 0,008) and job stress (P value = 0,006) of nurses with hand hygiene compliance. Multivariate logistic regression showed that workload (P value = 0,063) and job stress (P value = 0,039) had significant relationship with hand hygiene complince among nurses which job stress as dominant variable influencing compliance. Nurses should do relaxation to reduce job stress while facing Pandemi COVID-19.